2013
DOI: 10.1093/jpepsy/jst011
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Pain Catastrophizing Mediates the Relationship Between Protective Parental Responses to Pain and Disability Over Time

Abstract: Parental protectiveness is associated with disability indirectly through pain catastrophizing at the initial visit and follow-up. Decreases in parent protectiveness, potentially initiated through the initial evaluation, were related to lower levels of disability at follow-up through pain catastrophizing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
2
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 52 publications
3
47
2
2
Order By: Relevance
“…Parental protectiveness was shown to be associated with child disability indirectly through pain catastrophizing at initial visit and follow up, and decreases in parent protectiveness were related to lower levels of disability. This supports the Social Learning Theory, which asserts that an individual's responses are shaped via positive or negative reinforcement (Welkom et al 2013). Kraljevic et al (2012) also found significant positive correlation between pain catastrophizing of adult children and both of their parents.…”
Section: Parent and Child Relationshipssupporting
confidence: 72%
See 2 more Smart Citations
“…Parental protectiveness was shown to be associated with child disability indirectly through pain catastrophizing at initial visit and follow up, and decreases in parent protectiveness were related to lower levels of disability. This supports the Social Learning Theory, which asserts that an individual's responses are shaped via positive or negative reinforcement (Welkom et al 2013). Kraljevic et al (2012) also found significant positive correlation between pain catastrophizing of adult children and both of their parents.…”
Section: Parent and Child Relationshipssupporting
confidence: 72%
“…In support of the presentation of catastrophizing as a learned behavior are two recent studies by Welkom et al (2013), Kraljevic et al (2012). In these studies it was revealed that while a child's pain catastrophizing might have every intention of eliciting heightened assistance and empathetic parental responses, protective parenting is in fact particularly unhelpful.…”
Section: Parent and Child Relationshipsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, parental catastrophizing about their child's pain has been shown to be associated with child cognitions about pain, which in turn are related to the child's pain-related disability (e.g., Vowles, Cohen, McCracken, & Eccleston, 2010;Wilson, Lewandowski, & Palermo, 2011). The indirect effect of parent responses to children's pain has been demonstrated longitudinally, with adolescent cognitions, specifically catastrophizing, mediating the effect of parent protectiveness on pain and disability over time (Welkom, Hwang, & Guite, 2013). Child catastrophizing has consistently been shown to be associated with the experience of pain in children and adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…26 In regards to pain rehabilitation, pain catastrophizing was associated with greater functional disability, both at admission and 2 months following rehabilitation. 32 Pain catastrophizing has also been shown to be related to perceived pain intensity, functional disability, and general or trait anxiety, and to predict pain intensity and functional disability 6 months later. 33 Interestingly, others have shown pain catastrophizing to be related to psychological functioning and pain intensity, but not to functional impairment or social functioning.…”
mentioning
confidence: 99%